Some New Connection Relations Related to Classical Orthogonal Polynomials - Wathek Chammam; Wasim Ul-Haq (Journal of Mathematics)
In this paper, we deal with a problem of positivity of linear functionals in the linear space ℙ of polynomials in one variable with complex coefficients. Some new results of connection relations between the corresponding sequences of monic orthogonal polynomials of classical character are established.